Hydraulic architecture, water relations and vulnerability to cavitation of Clusia uvitana Pittier a C3 -CAM tropical hemiepiphyte - Zotz, Gerhard (The New phytologist, 1994)
Clusia uvitana Pittíer (Clusiacea) is a tropical hemiepiphyte that has been shown to display a high plasticity in the expression of CAM in response to the environment. When water is available CO2 is taken up mostly during the- day. This study of the water relations and hydraulic architecture has revealed that leaf water potentials, £ ranged from 0-7 to -0.9 MPa and changed very little with time or water availability. The absolute hydraulic conductivity of stem segments (K,) and the specific conductivity (K1 ) were comparable to many other temperate and tropical species, but the leaf specificity conductivity (K1 ) was 1/3 to 1/30 that of many other species. So stems supported high leaf areas per unit of hydraulic conductivity. C uvitana was very vulnerable to cavitation, reaching 50 % loss of hydraulic conductivity at stem £=1.3 MPa. The species survives in spite of low K1 and high xylem vulnerability, because the CAM physiology insures low transpiration rates and high ability to evade dehydration